The effects of binge-pattern alcohol consumption on orthodontic tooth movement - Araujo,Cristiano Miranda de (2014)
OBJECTIVE: This study aimed to assess tissue changes during orthodontic movement after binge-pattern ethanol 20% exposure.METHODS: Male Wistar rats (n = 54) were divided into two groups. The control group (CG) received 0.9% saline solution, while the experimental group (EG) received 20% ethanol in 0.9% saline solution (3 g/kg/day). On the 30th day, a force of 25 cN was applied with a nickel-titanium closed coil spring to move the maxillary right first molar mesially. The groups were further divided into three subgroups (2, 14 and 28 days). Tartrate-resistant acid phosphatase and picrosirius were used to assess bone resorption and neoformation, respectively. Data were compared by two-way ANOVA, Tukey's HSD, Games-Howell and chi-square test. Significance level was set at 5%.RESULTS: There was a decrease in the number of osteoclasts in EG at day 28. The percentage of collagen showed no interaction between group and time.CONCLUSION: Binge-pattern 20% ethanol promoted less bone resorption at the end of tooth movement, thereby suggesting delay in tooth movement.